Effect of melatonin on sleep quality and EEG features in childhood epilepsy: a possible non-conventional treatment - Dell'Isola, Giovanni Battista; Tascini, Giorgia; Vinti, Valerio; Tulli, Eleonora; Dini, Gianluca; Mencaroni, Elisabetta; Ferrara, Pietro; Di Cara, Giuseppe; Striano, Pasquale; Verrotti, Alberto (Frontiers in Neurology, 2023)
Background Sleep and epilepsy are characterized by a bidirectional relationship. Indeed, epilepsy predisposes to the development of sleep disorders, while sleep deprivation may exacerbate epilepsy. In addition, antiseizure medication can disrupt normal sleep architecture. Therefore, adequate sleep hygiene could lead to improvement in seizure control. The present study aimed to evaluate the effect of melatonin on seizure frequency, EEG tracing, and sleep in children with focal idiopathic epilepsy. Methods This observation study evaluated the effect of 4 mg oral melatonin in ameliorating sleep–wake cycle, seizure frequency, and EEG features in children with focal idiopathic epilepsy of infancy. Twenty children were enrolled from September 2020 to August 2021. The study consisted of serial controls at enrollment (t0), at 3 months (t1), and at 6 months (t2) including neurological examination, questionnaire about sleep disturbances (CSHQ), and EEG. Results A significant improvement in sleep quality and daytime sleepiness was observed after melatonin supplementation. Furthermore, we observed a noteworthy improvement in EEG tracing at t2 that exhibited a significant correlation with improvements in CSHQ scores. Conclusion The studies conducted so far to evaluate the effect of melatonin in persons with epilepsy do not lead to definitive conclusions. Despite the small population sample and the study design, we report sleep and EEG improvement after melatonin administration in our cohort. Larger studies are needed to further study the neuroprotective and anticonvulsant properties of melatonin.